Examining who benefits, in what ways, and in what contexts from Mine Action in the Lao People's Democratic Republic and Kurdish Iraq - Durham, M. Joanne (Curtin University, 2012)
Following violent conflict, the continued presence of landmines and unexploded ordnance (UXO) and other explosive remnants of war (ERW) pose a barrier to rebuilding livelihoods. Mine action (MA) or humanitarian demining by the international community removes explosive remnants of conflict to enable affected households and communities to safely return contaminated land to productive use.Informed by a realist approach to evaluation and using the livelihoods framework, this study undertaken in Lao People’s Democratic Republic (PDR) and the Kurdish Region of Iraq explored the outcomes of MA at the household level and the contextual factors which mediated the extent to which demined land was used and livelihood impacts sustained. The underlying assumption was that the transfer of decontaminated land to households would act as an incentive for households to use the land in ways which would have multiplier effects on other livelihood asset holdings but that access to these assets would be mediated by context.A mixed-methods design constituting a survey and qualitative interviews was selected for this study. The study was conducted in three phases. Phase 1 was undertaken in the Mines Advisory Group (MAG) program in the Lao People's Democratic Republic (PDR). Phase 2 was undertaken in MAG’s program in the Kurdish Region of Iraq. The National Regulatory Authority in Lao PDR provided the setting for Phase 3 of the study conducted first in Nong District and then in Paksong and Pek Districts. The qualitative component of the study explored the livelihood outcomes of mine action and contextual variables which mediated outcomes.A livelihood asset scale was developed and validated during this study. In the third phase the greatest reported change in access to assets was reported to be in human and physical assets. This was also reflected in the type of post clearance land use which was often for improved schools and community facilities. The qualitative data in each phase, but particularly in the first and second phases, suggested that demining also enabled program recipients to connect with important cultural symbols and rituals, contributing to building self-esteem and collective resilience. The qualitative data revealed that major factors influencing outcomes were: 1) household context and access to assets, 2) the environment, 3) organisational capacity and 4) institutional arrangements.In conclusion, the research makes a significant contribution in understanding how (MA) contributes to post-conflict recovery. It also made a significant contribution to the development of a livelihood asset scale which can be used to measure self-reported changes in household livelihood assets following a mine action intervention. The research has policy implications for MA in the sites of inquiry and of global relevance and suggests further avenues for research.